Gene amplification‐driven RNA methyltransferase KIAA1429 promotes tumorigenesis by regulating BTG2 via m6A‐YTHDF2‐dependent in lung adenocarcinoma. Issue 7 (21st June 2022) - Zhang, Chang; Sun, Qi; Zhang, Xu; Qin, Na; Pu, Zhening; Gu, Yayun; Yan, Caiwang; Zhu, Meng; Dai, Juncheng; Wang, Cheng; Li, Ni; Jin, Guangfu; et al.
Abstract: Background: Epigenetic alterations have been shown to contribute immensely to human carcinogenesis. Dynamic and reversible N6‐methyladenosine (m6A) RNA modification regulates gene expression and cell fate. However, the reasons for activation of KIAA1429 (also known as VIRMA, an RNA methyltransferase) and its underlying mechanism in lung adenocarcinoma (LUAD) remain largely unexplored. In this study, we aimed to clarify the oncogenic role of KIAA1429 in the tumorigenesis of LUAD. Methods: Whole‐genome sequencing and transcriptome sequencing of LUAD data were used to analyze the gene amplification of RNA methyltransferase. The in vitro and in vivo functions of KIAA1429 were investigated. Transcriptome sequencing, methylated RNA immunoprecipitation sequencing (MeRIP‐seq), m6A dot blot assays and RNA immunoprecipitation (RIP) were performed to confirm the modified gene mediated by KIAA1429. RNA stability assays were used to detect the half‐life of the target gene. Results: Copy number amplification drove higher expression of KIAA1429 in LUAD, which was correlated with poor overall survival. Manipulating the expression of KIAA1429 could regulate the proliferation and metastasis of LUAD. Mechanistically, the target genes of KIAA1429‐mediated m6A modification were confirmed by transcriptome sequencing and MeRIP‐seq assays. We also revealed that KIAA1429 could regulate BTG2 expression in an m6A‐dependent manner. Knockdown of KIAA1429 significantly decreased the m6A levels of BTG2 mRNA, leading to enhanced YTH m6A RNA binding protein 2 (YTHDF2, the m6A "reader")‐dependent BTG2 mRNA stability and promoted the expression of BTG2; thus, participating in the tumorigenesis of LUAD. Conclusions: Our data revealed the activation mechanism and important role of KIAA1429 in LUAD tumorigenesis, which may provide a novel view on the targeted molecular therapy of LUAD.